The Consolidated Medium-Term Income and Expenditure Framework. (Policy Papers; Policy Paper ;, 2013)
The medium-term projections of Fund income and precautionary balances accumulation have been updated since the April 2012 projections. The overall income outlook remains positive with continued high lending income expected in the medium-term. The projections indicate a downward shift in the income path primarily due to lower non-lending income as a result of the low global interest rates and the agreement to phase in investments under the new gold-sales funded endowment. The updated expenditure path has not changed significantly. The projections also illustrate a broad balance between income and expenditures when lending returns to pre-crisis levels. The accumulation of precautionary balances remains strong in the medium-term. The indicative medium-term target of SDR 20 billion is now expected to be reached by FY18-FY19.